A Novel Human Acute Encephalitis Caused by Pseudorabies Virus Variant Strain. (15th July 2020) - Liu, Qingyun; Wang, Xiaojuan; Xie, Caihua; Ding, Shifang; Yang, Hongna; Guo, Shibang; Li, Jixuan; Qin, Lingzhi; Ban, Fuguo; Wang, Dongfang; Wang, Cui; Feng, Lingxiao; et al.
Abstract: Background: Pseudorabies virus (PRV) is a common pathogen in multiple animal species, particularly in pigs. However, PRV infection in humans is rare and, to the best of our knowledge, PRV has never been isolated from human cases before. Methods: Four acute encephalitis cases in humans were confirmed as PRV infection based on clinical symptoms, laboratory diagnosis, and metagenomic next-generation sequencing (mNGS). Cerebrospinal fluid (CSF) samples were collected and applied for virus isolation. Etiological and genetic characteristics of this PRV human isolate were further determined. Results: The patients manifested respiratory dysfunction and acute neurological symptoms. The mNGS revealed PRV-specific nucleotide sequences in patients' CSF samples (7–6198 reads and 0.2446%–80.58% coverage). The PRV envelope glycoprotein B antibody, glycoprotein E antibody, and neutralizing antibody were positively detected. For the first time, a PRV strain, designated hSD-1/2019, was isolated and identified from a CSF sample, and transmission electron microscopy revealed that hSD-1/2019 had typical morphology similar to that of swine PRV. Phylogenetic analysis illustrated that hSD-1/2019 was genetically closest to those PRV variant strains currently circulating in pigs in China, and this strain showed similar etiological characteristics to Chinese PRV variant strains, while different from Chinese classical strain. Moreover, hSD-1/2019 showed high pathogenicity and induced acute neurological symptoms in pigs. Conclusions: A PRV strain was isolated from an acute human encephalitis case. This isolate showed close phylogenetic relationships and similar etiological characteristics to Chinese PRV variant strains, implying the great risk of PRV transmission from pigs to humans. Abstract : This report describes 4 confirmed acute human encephalitis cases caused by pseudorabies virus (PRV). One PRV strain was first isolated from a patient and showed close phylogenetic relationship and similar etiological characteristics to Chinese PRV variant strains.